Notes on the geology and geomorphology of the Carey Øer, Nort-West Greenland - Bendix-Almgreen, Svend E.; Fristrup, Børge; Nichols, Robert L. (Meddelelser om Grønland, 1967)
The Carey Øer, a group of small islands, is located in the southern part of Smith Sound, North-West Greenland. The largest of the islands, Nordvestø, was investigated. It consists, as do apparently all the islands in the group, of Precambrian metamorphic rocks dominated by grey, banded gneiss and pink gneiss. Doleritic dykes and sills occur. No sedimentary rocks occur in situ. A great number of glacial erratic boulders, identical with sedimentary rocks found in situ on the mainland and on Saunders 0 east of the islands, are present. As indicated by the erratics, the islands were covered by the Greenland ice sheet, but local glacial ice may have occurred both before and after they were covered by the Greenland ice sheet. The geomorphological features suggest that the characteristic flat summit surfaces of the islands are remnants of the same late Pliocene or early Pleistocene erosion surface, which occurs on the neighbouring mainland and on Saunders Ø. The erosion surface was heavily dissected by fluvial action with the formation of steep cliffs. This was followed by a marine submergence which flooded the river valleys and produced the islands. Raised beaches are found in several places on Nordvestø and on Mellem0 and Isbj0rne0 as well. Periglacial features such as frost cracks, solifluction Jobes, frost mounds, frost-shattered rock, talus, permafrost, and snowbank trimlines are common.